Interpersonal Communication in Maintaining Marital Harmony : Ethnographic Study of Married Couples Aged 15-20 Years in Bekasi - Fitri Sarasati; Helen Olivia; Abdul Latief; Achmad Budiman Sudarsono (Journal of Content and Engagement, 2023)
Being married for 15-20 years is not easy. Various challenges experienced by couples can reduce marital harmony – the importance of good communication between couples to keep the relationship from being damaged. This research uses Relational Maintenance Theory. This qualitative research uses the post-positivism paradigm and ethnographic methods, data collected through in-depth interviews, observations, and literature studies. The result of this study is that husband and wife often get differences in how to educate children, communication problems, and differences in character and culture. Communication is the first way couples solve problems, such as continuing to communicate using media when their partner is in a bad mood. Married couples also take several ways to maintain their marital relationship, such as openness, assurance, sharing duties, joint activities, and complementarity and understanding. Interpersonal communication carried out by married couples with a marriage age of 15-20 years is quite good, and they can maintain the harmony of their marriage to date.